Places of learning, imprisoned bodies and spaces of freedom in 19th and 20th century children's literature - Lorenzo Cantatore (University of Bologna, 2017)
Awareness of the close relationship between body, mind and space has recently become a much-discussed issue in educational theory and historical-educational research. This is especially true within children's literature, which offers a host of insights into the nexus between these concepts. Between the 19th and 20th centuries, a number of authors wrote stories about children who were conditioned, both positively and negatively, by the spaces in which their adventures unfolded, with the home being the perfect embodiment of a spatial representation of education. In the history and practice of play, the idea of "home" contains examples of great pedagogical interest. The contrast between care and forced domestication places children, in terms of how they are represented artistically and historically, at the center of a process brimming with contradictions and moral and emotional tension, all of which are linked specifically to the spaces in which they are born and raised.